The CDC blood lead reference value for children: time for a change - Jerome A. Paulson; Mary Jean Brown (BMC, 2019)
Abstract The purpose of this article is to consider alternate uses of the blood lead reference value for children. There are two possible approaches. Historically the reference value has been used to guide clinical and public interventions for individual children. As the distribution of blood lead levels in the population has been lowered over time, the blood lead level at which interventions are recommended has also been reduced. The use of a reference value of 3.5 μg/dL, based on the 98 percentile of blood lead levels for children in 2011-2014 National Health and Nutrition Examination Survey is under review. For several reasons, adopting the new reference value to guide clinical and public health management puts practitioners in an untenable position. First, the changes in the brain caused by lead are significant and persistent. However, these adverse impacts are subtle and although clearly identified at the population level, not predictive for individual children. In addition, the recommended interventions have not been shown to reduce blood lead levels once they are elevated. Finally, clinical laboratory and office-based blood lead testing devices are not required to quantify blood lead levels < 4 μg/dL and in many cases cannot reliably test for low blood lead levels. Revising the reference value also will undoubtedly result in diversion of resources away from those population-based interventions which have demonstrated success. We argue for second approach, in the management of lead poisoning in the US from one of evaluation and management at the individual level to one of population based primary prevention. This would require a strategy directed at controlling or eliminating lead in children's environment before they are exposed. The reference value, as a benchmark, is essential to ensure that primary prevention efforts are successful.